2023
DOI: 10.1101/2023.03.28.534017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex, single-cell CRISPRa screening for cell type specific regulatory elements

Abstract: CRISPR-based gene activation (CRISPRa) is a promising therapeutic approach for gene therapy, upregulating gene expression by targeting promoters or enhancers in a tissue/cell-type specific manner. Here, we describe an experimental framework that combines highly multiplexed perturbations with single-cell RNA sequencing (sc-RNA-seq) to identify cell-type-specific, CRISPRa-responsive cis-regulatory elements and the gene(s) they regulate. Random combinations of many gRNAs are introduced to each of many cells, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Although recent advances have shown that this task is tractable 60 , more work is in demand to achieve higher recovery of feature barcodes in sci-RNA-seq3 experiments, which critically underlies the scalability of this method. Finally, in the CRISPRa experiments, to achieve enduring activation of target genes, we utilized a cell line with integrated dCas9-VP64 57 , which could potentially compete with the prime editor for pegRNA binding, resulting in reduced concentrations of functional pegRNA and physical hindrance at prime editing target sites. Alternative strategies such as using in vitro assembled prime editing RNPs or orthogonal CRISPRa systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent advances have shown that this task is tractable 60 , more work is in demand to achieve higher recovery of feature barcodes in sci-RNA-seq3 experiments, which critically underlies the scalability of this method. Finally, in the CRISPRa experiments, to achieve enduring activation of target genes, we utilized a cell line with integrated dCas9-VP64 57 , which could potentially compete with the prime editor for pegRNA binding, resulting in reduced concentrations of functional pegRNA and physical hindrance at prime editing target sites. Alternative strategies such as using in vitro assembled prime editing RNPs or orthogonal CRISPRa systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For gene activation, we chose the CRISPRa Synergistic Activation Mediator (SAM) system 56 . On Day 0, we transfected a K562 cell line stably expressing the dCas9-VP64 fusion 57 with a pair of gRNAs (2XMS2) targeting the promoter of one of these four genes, along with an MCP-p65-Rta fusion protein. On Day 2, we transfected the cells with PEmax and pegRNAs to introduce the desired mutations (Fig.…”
Section: Modulating Prime Editing Outcomes By Targeted Epigenetic Rep...mentioning
confidence: 99%
“…To reiterate, the primary aim of our platform development has been to enable the discovery of novel endogenous regulators of therapeutic relevance, and then translate these native genes to common ORFs or rationally-designed synthetic genes, intended for CAR or other forms of adoptive T cell therapy. However, given their modularity and capacity for multiplex gene modulation, 73 we envision that CRISPRa + T cells could conceivably be offered, either as stand-alone or programmed, personalized GoF treatment options in due course. Indeed, private pharmaceutical companies have been founded, predicted on the development of in vivo CRISPRa drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The technology described here should likewise easily extend to combinatorial screens, such as activating multiple genes at their respective promoters, an approach that is extraordinarily useful to engineer cell types of interest and understand cell fate decisions. Further, scalable combinatorial screens can enable dissection of the regulatory logic of the non-coding genome, by jointly targeting potential enhancer elements and putative promoter targets 16,45 . In sum, we have demonstrated methods for implementing Cas12a-based CRISPRa at scale in human cells.…”
Section: Discussionmentioning
confidence: 99%